The Influence of Brand Image and Digital Marketing on Consumer Purchasing Decisions (Case Study on Roja Bouquet Flower Shop) - Bakti, Umar; Loliyani, Rini; Hairudin, Hairudin; Astrid Aprica Isabella; Loliyana, Rina; Adelita, Ira (International Journal of Economics (IJEC), 2024)
This research aims to determine the influence of Brand Image and Digital Marketing Attitudes on consumer purchasing decisions at the Roja Bouquet flower shop in Bandar Lampung. The type of data used in this research is quantitative, using primary and secondary data. To determine the research sample, we used a probability sampling technique because the population was above 100. The results of calculations using the Slovin formula produced a sample size of 70 respondents. The analysis technique used involves Validity, Reliability, Classical Assumptions and Hypothesis Tests. From the research results, we found that Brand Image and Digital Marketing together have a significant influence on consumer purchasing decisions at the Roja Bouquet flower shop. Brand Image and Digital Marketing have an influence of 48.9% on consumer purchasing decisions, while the remaining 51.1% is influenced by other factors not examined in this research.